The Symbolic Meaning of the Medhak Sanggring Tradition in Tlemang Village, Lamongan Regency - Dewi Pratiwi; Arief Sudrajat (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
The Mendhak Sanggring tradition is a cultural practice still maintained by the people of Tlemang Village, Lamongan. This tradition is seen as having spiritual, symbolic, and social values that are crucial for the continuity of community life. This study aims to uncover the meaning of the Mendhak Sanggring tradition through the perspective of Herbert Blumer's Symbolic Interaction, specifically by examining how this meaning is formed, maintained, and reinterpreted by the community. This study used a qualitative approach with descriptive methods. Data were obtained through in-depth interviews and documentation, then analyzed using an interactive analysis model that includes data reduction, data presentation, and conclusion drawing. The results show that the meaning of the Mendhak Sanggring tradition is formed through a process of social interaction that has been passed down through generations. This meaning is manifested in four main aspects: respect for ancestors, cultural identity and collective pride, safety and protection from disaster, and social harmony. Based on Blumer's Symbolic Interaction perspective, this meaning emerges through three premises: community actions are driven by the symbolic meaning inherent in tradition; these meanings emerge from social interactions between residents and traditional leaders; and they undergo continuous negotiation and reinterpretation as generations change. This research confirms that Mendhak Sanggring functions not only as a spiritual ritual but also as a mechanism for cultural reproduction and strengthening collective identity within the community.